2017
DOI: 10.1111/cas.13452
|View full text |Cite
|
Sign up to set email alerts
|

miR‐335 inhibited cell proliferation of lung cancer cells by target Tra2β

Abstract: Accumulating evidence has suggested that the dysregulation of miRNA is an important factor in the pathogenesis of lung cancer. Here, we demonstrate that miR‐335 expression is reduced in non‐small cell lung cancer (NSCLC) tumors relative to non‐cancerous adjacent tissues, while the expression of Tra2β is increased. In addition, clinical data revealed that the increased Tra2β and decreased miR‐335 expression observed in NSCLC cells was associated with poor patient survival rates. In vitro experimentation showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 26 publications
0
38
0
Order By: Relevance
“…Li et al found that miR-93-5p played an inhibitory role in the proliferation and metastasis of CC cells, and it could suppress the development of HPV-positive CC by targeting BTG3. 12 These studies suggest that the abnormal expression of miRNAs may affect the malignant progression of CC. It has been reported that miR-145-5p is down-regulated in a variety of human cancers, such as breast cancer 13 and bladder cancer 14 , and plays an inhibitory role in tumor growth.…”
Section: Introductionmentioning
confidence: 97%
“…Li et al found that miR-93-5p played an inhibitory role in the proliferation and metastasis of CC cells, and it could suppress the development of HPV-positive CC by targeting BTG3. 12 These studies suggest that the abnormal expression of miRNAs may affect the malignant progression of CC. It has been reported that miR-145-5p is down-regulated in a variety of human cancers, such as breast cancer 13 and bladder cancer 14 , and plays an inhibitory role in tumor growth.…”
Section: Introductionmentioning
confidence: 97%
“…In NSCLC, miRNAs may have potential roles in modulating metastases, either by inhibition or reconstitution of their functions [20]. In several human cancers, hsa-miR-335 has multiple roles in carcinogenesis [21][22][23][24]. Although little is known of the role of miR-335-3p in lung cancer, in several other cancers, miR-335-3p is down-regulated [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the Tra2b protein (the transformer 2 beta homolog) is particularly interesting as it is considered one of the most important splicing factors involved in RNA processing needed for both normal (e.g., brain development) and pathological (e.g., cancer) cell proliferation [75,76]. The RNA binding protein Rbmx, also known as heterogenous nuclear ribonucleoprotein G (hnRNPG), also functions as an important protein, being involved in the regulation of gene expression and alternative splicing.…”
Section: Discussionmentioning
confidence: 99%